Uso de la toxina botulínica en el tratamiento de sonrisa gingival - Lino Brancini, Mirilaini (2021)
The objective was to address the importance of using botulinum toxin to correct gummy smile, showing patient satisfaction even if the effect is temporary and reversible, avoiding invasive procedures. A bibliographic survey was carried out in the databases PubMed, LILACS and Bireme, the terms used in the research were gummy smile and botulinum toxin or gummy smile and aesthetic. The inclusion criteria were a review of the literature of clinical cases of patients with with a gummy smile published between 2015 and May 2019. This review addressed the application of botulinum toxin to give the patient a beautiful and harmonious smile, as it is a viable, efficient, less invasive and safe alternative. The practice of applying botulinum toxin can be a useful complement to improve patient satisfaction with a gummy smile without undergoing invasive procedures, that is, when well indicated, being able to replace or complement surgical procedures.